The daring Miss Quimby - Whitaker, Suzanne; Stock, Catherine (New York : Holiday House, 2009)
Describes Harriet Quimby's success as the first woman in the United States to earn a pilot's license and the public's admiration of her.
Includes bibliographical references.
3.6
K-3
Keywords: Quimby, Harriet, -- 1875-1912 -- Juvenile literature; Quimby, Harriet, -- 1875-1912.; Quimby, Harriet, -- 1875-1912.; Women air pilots -- United States -- Biography -- Juvenile literature; Air pilots -- United States -- Biography -- Juvenile literature; Women air pilots; Air pilots; Women -- Biography; Women air pilots -- United States -- Biography; Air pilots -- Biography; Women -- Biography; Women air pilots -- Biography; Air pilots -- United States -- Biography; Picture books for children